Estrutura e relações florísticas entre campos de murundus do Vale do Guaporé, Rondônia e Brasil Central - Paêlo, Mônica Gabrielle (2013)
Earthmound field is a savanna types characterized by the occurrence of mounds in the presence of flora shrub and tree free flood spread over a grassy field matrix seasonally waterlogged or flooded. The present study aimed to characterize the earthmound fields of flood plains Guapore in terms of physiognomy and floristic and compare them to earthmounds fields being studied and the literature, situated in the flood plains of the Pantanal, Araguaia, Bananal and plateaus of Brazil Central.. The work was carried out at the Parque Estadual Corumbiara (PEC), Rondônia. We studied four earthmounds fields of one hectare each. All earthmounds were counted and measured (length, width and height). All species on mounds with stem diameter at breast height ≥ 5 cm were sampled. The Herbaceous grassland matrix were sampled at 250 points on an axis by earthmound. To check relations with nine other areas of Central Brazil was the method used by TWINSPAN classification. We recorded a total of 620 mounds, with an average density of 155 mounds / ha, average area of 15 m2 and an average height of 0.55 m, with smaller area and higher density and height than earthmounds on the plateau of Central Brazil. We recorded 29 botanical families, 50 genera and 60 species, 41 in the woody layer and 19 in the herbaceous layer. The families with greater wealth were Poaceae and Fabaceae. Were recognized three groups of earthmounds fields mounds by TWINSPAN groups from the core region of the Cerrado, flood plains of central Brazil and floodplain of Guapore in area of cerrado enclave within the Amazon biome. The separation of these groups is associated with differences in the floristic composition of each locality. This was the first survey work flora and physical characterization of earthmounds fields in the floodplain of the Guapore. This study is required to facilitate the development of specific regulations, adjusted to the peculiarities presented by these environments, contributing to the conservation of these areas.